2004
DOI: 10.1023/b:boli.0000028781.94251.1f
|View full text |Cite
|
Sign up to set email alerts
|

Executive function impairment in early‐treated PKU subjects with normal mental development

Abstract: Executive functions were studied in 14 early and continuously treated PKU subjects (age 10.8 years, range 8-13) in comparison with controls matched for IQ, sex, age and socioeconomic status. Brain MRI examination was normal in all PKU patients. Neuropsychological evaluation included Wisconsin Card Sorting Test, Rey-Osterreith Complex Figure Test, Elithorn's Perceptual Maze Test, Weigl's Sorting Test, Tower of London, Visual Search and Motor Motor Learning Test. Whatever the IQ, PKU subjects performed worse tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
17

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 34 publications
3
74
0
17
Order By: Relevance
“…Dicho de otro modo, los pacientes con FCU tratados precozmente tienden a necesitar más tiempo para procesar información y completar tareas que los controles y, en consecuencia, son más lentos en su respuesta a estímulos, cuando eligen entre objetivos o cuando completan actividades simples o complejas. A pesar del peso de las pruebas que permiten suponer una reducción de la eficiencia del procesamiento en los pacientes afectados de FCU [5,14,41,51] , debe puntualizarse que también existe investigación contradictoria [7,26,52] . El procesamiento de información más lento puede tener implicaciones significativas sobre la codificación y el almacenamiento de nueva información y la función ejecutiva.…”
Section: Procesamiento De La Informaciónunclassified
See 3 more Smart Citations
“…Dicho de otro modo, los pacientes con FCU tratados precozmente tienden a necesitar más tiempo para procesar información y completar tareas que los controles y, en consecuencia, son más lentos en su respuesta a estímulos, cuando eligen entre objetivos o cuando completan actividades simples o complejas. A pesar del peso de las pruebas que permiten suponer una reducción de la eficiencia del procesamiento en los pacientes afectados de FCU [5,14,41,51] , debe puntualizarse que también existe investigación contradictoria [7,26,52] . El procesamiento de información más lento puede tener implicaciones significativas sobre la codificación y el almacenamiento de nueva información y la función ejecutiva.…”
Section: Procesamiento De La Informaciónunclassified
“…Aunque algunos investigadores no han sido capaces de identificar dichos deterioros utilizando mediciones cognitivas de la FE [31,58,68] , otros han registrado peores rendimientos en pacientes con FCU [26,44] . Por ejemplo, en la tarea Torre de Londres, una medición tradicional de la planificación y organización, los niños afectados de FCU han revelado deterioros significativos del tiempo de planificación y ejecución [64] .…”
Section: Función Ejecutiva (Fe)unclassified
See 2 more Smart Citations
“…In another study, Ris and colleagues compared the neuropsychological performance of adults affected by PKU with that of their unaffected siblings and found that the PKU patients were relatively impaired on measures of attention, visual-constructional ability, and cognitive flexibility [22]. Leuzzi and colleagues [15] showed that young subjects with earlytreated PKU performed worse in comparison to age and IQ matched controls on various tasks including tower of London (TOL), Visual Search Test, Rey-Osterreith Complex Figure Test, Weigl's Sorting Test, and Motor Learning Test indicating problems with planning and problem solving, set shifting, selective and sustained attention and sorting of categories.…”
Section: Introductionmentioning
confidence: 99%